2007
DOI: 10.1124/jpet.107.127209
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulatory Treatment of Trinitrobenzene Sulfonic Acid Colitis with Calcitriol Is Associated with a Change of a T Helper (Th) 1/Th17 to a Th2 and Regulatory T Cell Profile

Abstract: A number of recent studies testify that calcitriol alone or in combination with corticosteroids exerts strong immune modulatory activity. As a new approach, we evaluated the protolerogenic potential of calcitriol and dexamethasone in acute T helper (Th)1-mediated colitis in mice. A rectal enema of trinitrobenzene sulfonic acid (TNBS) (100 mg/kg) was applied to BALB/c mice. Calcitriol and/or dexamethasone were administered i.p. from days 0 to 3 or 3 to 5 following the instillation of the haptenating agent. Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
313
2
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(333 citation statements)
references
References 36 publications
11
313
2
7
Order By: Relevance
“…Conversely treatment with 1,25(OH) 2 D improves IBD symptoms and blocks the progression of colitis in mice (65,70,71) Vitamin D may also function on the epithelial barrier. Epithelial cells are connected by intercellular junctions, comprising tight junctions and adherens junctions (72) .…”
Section: Vitamin D and Immune Function In Crohn's Disease: Experimentmentioning
confidence: 99%
“…Conversely treatment with 1,25(OH) 2 D improves IBD symptoms and blocks the progression of colitis in mice (65,70,71) Vitamin D may also function on the epithelial barrier. Epithelial cells are connected by intercellular junctions, comprising tight junctions and adherens junctions (72) .…”
Section: Vitamin D and Immune Function In Crohn's Disease: Experimentmentioning
confidence: 99%
“…Our findings, together with previous in vitro-gained data that VD regulates the expression of IL-17 and TNFα in immune cells, suggest that VD action on Th17 cells represents at least one of the mechanisms controlling inflammation in CVD. VD can directly decrease IL-17 production, by its main source, the Th17 cells 30 , and impair their differentiation 31,32 . Importantly, IL-17 is an inducer of proinflammatory cytokine IL-6 and TNFα specifically in the heart 10 .…”
Section: Chf Patientsmentioning
confidence: 99%
“…3 Furthermore, Th17 cells, a novel helper T-cell lineage with characteristics of secreting IL-17, recently have been identified to participate in the pathogenesis of CD and TNBS colitis. 37,38 To address whether blocking C5a contributes to downregulating Th1/Th17 responses, lymphocytes of mesenteric lymph nodes from different groups at 4 days after TNBS instillation were isolated and stimulated with anti-CD3/anti-CD28. We found that the induction of colitis apparently augmented Th1/Th17 responses (Figure 6a), characterized by secreting large amounts of IFN-g and IL-17, respectively.…”
Section: Blockade Of C5a Avtivity Inhibits Th1/th17 Responses and Elimentioning
confidence: 99%